Circuit breakers as market stability levers: A survey of research, praxis, and challenges. (29th October 2018) - Sifat, Imtiaz Mohammad; Mohamad, Azhar
Abstract: Circuit breaker, an automated regulatory instrument employed to deter panic, temper volatility, and prevent crashes, is controversial in financial markets. Proponents claim it provides a propitious time out when price levels are stressed and persuades traders to make rational trading decisions. Opponents demur its potency, dubbing it a barrier to laissez‐faire price discovery process. Since conceptualization in 1970s and practice from 1980s, researchers focused mostly on its ability to allay panic, interference in trading, volatility transmission, prospect of self‐fulfilling prophecy through gravitational pull towards itself, and delayed dissemination of information. Though financial economists are forked on circuit breakers' usefulness, they are a clear favourite among regulators, who downplay the reliability of anti‐circuit breaker findings citing, inter alia, suspect methodology, and lack of statistical power. In the backdrop of 2007–2008 Crisis and 2010 Flash Crash, the drumbeats for more regulatory intervention in markets grew louder. Hence, it is unlikely that intervening mechanism such as circuit breakers will ebb. But are circuit breakers worth it? This paper synthesizes three decades of theoretical and empirical works, underlines the limitations, issues, and methodological shortcomings undermining findings, attempts to explain regulatory rationale, and provides direction for future research in an increasingly complex market climate.